2021
DOI: 10.1002/jia2.25763
|View full text |Cite
|
Sign up to set email alerts
|

Maternal weight and birth outcomes among women on antiretroviral treatment from conception in a birth surveillance study in Botswana

Abstract: Introduction Antiretrovirals such as dolutegravir (DTG) and tenofovir alafenamide (TAF) have been associated with excessive weight gain. The objective of this study was to understand the potential impact of ART‐associated weight gain on pregnancy outcomes among women living with HIV. Methods Using data from the Tsepamo birth outcomes surveillance study in Botswana, we evaluated the relationship between maternal weight (and weight gain) and severe birth outcomes (very preterm delivery <32 weeks, very small for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…An analysis based on Scottish national data in 1999-2009 estimated that the population attributable fraction of maternal current smoking for neonatal death was 6.7% [50]. Whilst prepregnancy weight and pregnancy weight gain (inadequate to excessive) in WLWH are current topics of interest, particularly in relation to type of antiretroviral regimen [53,54], the prevalence of obesity in pregnant WLWH in the UK is uncertain, but may be expected to be high based on a prevalence of 38% of WLWH in one English study [55]. This may be of concern, given that a large meta-analysis reported a moderate increase in relative risk (RR) of neonatal death per 5 unit increase in maternal body mass index (BMI) (RR 1.15, 95% CI 1.07, 1.23) [56].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis based on Scottish national data in 1999-2009 estimated that the population attributable fraction of maternal current smoking for neonatal death was 6.7% [50]. Whilst prepregnancy weight and pregnancy weight gain (inadequate to excessive) in WLWH are current topics of interest, particularly in relation to type of antiretroviral regimen [53,54], the prevalence of obesity in pregnant WLWH in the UK is uncertain, but may be expected to be high based on a prevalence of 38% of WLWH in one English study [55]. This may be of concern, given that a large meta-analysis reported a moderate increase in relative risk (RR) of neonatal death per 5 unit increase in maternal body mass index (BMI) (RR 1.15, 95% CI 1.07, 1.23) [56].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancies were categorized as having DTG or any INSTI exposure if a mother received these drugs at any time between conception and delivery. ART was categorized by timing of receipt, in the first (gestational age �13 weeks), second (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), or third (28-delivery) trimesters.…”
Section: Data Managementmentioning
confidence: 99%
“…In contrast, the SMARTT study identified a 2-fold higher rate of preterm birth among infants with first-trimester INSTI exposure compared to no INSTI exposure [18]. Few studies have compared maternal outcomes such as preeclampsia, gestational diabetes, and laboratory abnormalities between pregnancies exposed to INSTIs versus other ART [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of both chronic and new-onset HDP in this cohort were slightly higher than that found in population-based cohorts of pregnant individuals without HIV, which have demonstrated a gradual rise in the occurrence of both conditions [23][24][25][26] U.S. data have suggested, as we hypothesized, that INSTI use may be associated with an elevated risk of HDP compared with protease-inhibitor-based regimens [9]. In Southern Africa, findings from the Botswana-based Tsepamo study found the prevalence of maternal hypertension to be higher with dolutegravir versus efavirenz-based regimens, with the ART regimen acting as an effect modifier of the relationship between weight and hypertension [28]. Recent findings from a cohort of 794 pregnant PWH in Italy demonstrated no difference in hypertension by ART category [29].…”
Section: Discussionmentioning
confidence: 82%